Prevention of chronic complications of diabetes mellitus according to complexity - Maria Aparecida Salci; Betina Hörner Schlindwein Meirelles; Denise Maria Vieira Guerreiro da Silva
ABSTRACT Objective: To assess the prevention by primary health care providers of chronic complications of diabetes mellitus according to the complex thinking theoretical approach. Method: Evaluative research based on the complex thinking theoretical approach. The following techniques for data collection were used: interviews with 38 participants; observation in collective and individual appointments; and analysis of medical records of people with diabetes. The triangulation applied for data analysis was the ATLAS.ti software. Results: The prevention and management of chronic complications of diabetes did not meet the requirements set forth by ministerial public policies aimed at this population. Systematic monitoring to prevention of chronic complications showed significant gaps. Final considerations: Primary health care did not consider preventive actions for diabetes mellitus complications. This context was marked by disjunctive, fragmented, and dissociated practices types of care targeted to the totality of the assisted people.